Perspective ways of development aeronavigation in the beginning of the XXI century - Харченко, В. П. (Proceedings of National Aviation University (archive), 2003)
Strategic ways of development aerospace information systems are considered. Main attention is given to global system of communication, navigation, observation and organization of aircraft’s air motion